2020
DOI: 10.1155/2020/1464098
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Cancellation of Elective Surgical Procedures at a Tertiary Hospital in Uganda: A Cross-Sectional Study

Abstract: Introduction. The cancellation of elective procedures has been shown to waste resources and to have the potential to increase morbidity and mortality among patients. This study aimed to determine the prevalence of the cancellation of elective surgical procedures and to identify the factors associated with these cancellations at Mulago Hospital, a large public hospital in Kampala, Uganda. Methods. A cross-sectional study was conducted from January 10, 2018, to February 20, 2018. We recruited patients of all age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
26
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 21 publications
(19 reference statements)
5
26
7
Order By: Relevance
“…Besides, management strategies or surgical settings might be similar in developing countries. However, the current study's finding is lower than a study conducted in Nigeria [23], Uganda [35] and Malawi [21]. This Table 2 Characteristics of included studies in the meta-analysis for the root causes of elective surgical case cancellation discrepancy might be due to findings of elective surgery cancellation vary widely because of study design; type of hospital, country, capacity, and patient type (inpatients vs. outpatients).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Besides, management strategies or surgical settings might be similar in developing countries. However, the current study's finding is lower than a study conducted in Nigeria [23], Uganda [35] and Malawi [21]. This Table 2 Characteristics of included studies in the meta-analysis for the root causes of elective surgical case cancellation discrepancy might be due to findings of elective surgery cancellation vary widely because of study design; type of hospital, country, capacity, and patient type (inpatients vs. outpatients).…”
Section: Discussioncontrasting
confidence: 66%
“…Based on the estimation of the root causes for elective surgical case cancellation, the most common identified cause was administration-related reason. The same report from the Kingdom of Saudi Arabia [17], Jordan [18], Uganda [35], and Malawi [21] showed that administration-related reasons found the most common causes of elective surgical case cancellation. This might be due to the reality is that surgical case cancellation can result in the financially under-utilization of theatres [2].…”
Section: Discussionmentioning
confidence: 98%
“…The subgroup analysis also showed that the prevalence of cancellation was the highest in Sub-Saharan African region [ 5 , 15 , 25 , 35 , 56 , 63 ] 34% (95% confidence interval (CI): 26 to 42) followed by Latin America [ 14 , 43 , 47 , 51 , 53 , 59 , 66 ] 13% (95% confidence interval (CI): 8 to 19) were Burkina Faso and Ethiopia accounted for more than fifty percent from African region [ 5 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, management strategies or surgical settings might be similar in developing countries, but lower than a study conducted in Nigeria [23], Uganda [35] and Malawi [21]. This discrepancy might be due to ndings of cancellation varying widely by study design; hospital type, country, and capacity; patient type (inpatients vs. outpatients).…”
Section: Discussionmentioning
confidence: 90%
“…Based on the estimation of the reason for elective surgical case cancellation, the most common identi ed reason was administration-related reasons. The same report from the Kingdom of Saudi Arabia [17], Jordan [18], Uganda [35], and Malawi [21] showed that administration-related reasons found the most common reasons of elective surgical case cancellation. This might be due to the reality is that surgical case cancellation can result in the nancially under-utilization of theatres [2].…”
Section: Discussionmentioning
confidence: 97%